2017
DOI: 10.1016/j.ceca.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin exocytosis by calcium-dependent protein kinase C in beta cells

Abstract: The control of insulin release from pancreatic beta cells helps ensure proper blood glucose levels, which is critical for human health. Protein kinase C has been shown to be one key control mechanism for this process. After glucose stimulation, calcium influx into beta cells triggers exocytosis of insulin-containing dense-core granules and activates protein kinase C via calcium-dependent phospholipase C-mediated generation of diacylglycerol. Activated protein kinase C potentiates insulin release by enhancing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 163 publications
0
21
0
1
Order By: Relevance
“…Exocytosis is dependent on the formation of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex. This complex is composed of three main components: the vesicle-bound VAMP2, which binds to two target membrane proteins, syntaxin1A and SNAP25 (45). It was shown that SNAP25 in neuronal cells can directly interact with the conventional Gβγ complexes, influencing neurotransmitter release (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Exocytosis is dependent on the formation of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex. This complex is composed of three main components: the vesicle-bound VAMP2, which binds to two target membrane proteins, syntaxin1A and SNAP25 (45). It was shown that SNAP25 in neuronal cells can directly interact with the conventional Gβγ complexes, influencing neurotransmitter release (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic β-cells express several isoforms of PKC, which are thought to play different roles in GSIS (Trexler and Taraska, 2017). They are activated during high glucose conditions and influence insulin exocytosis by activating components of the exocytotic machinery.…”
Section: Pkc Is Responsible For Endosomal Degradation and Downregulamentioning
confidence: 99%
“…The second phase is associated with an increased production of DAG (Wolf et al, 1990) and activation of several PKC isoforms (,β, and ) in the β-cell (Trexler and Taraska, 2017;Warwar et al, 2006). The different PKC isoforms appear to target different components of machinery associated with insulin secretion (Trexler and Taraska, 2017). In relation to the KATP channel, an yet-to-be identified PKC isoform activates the channel via threonine180 phosphorylation at Kir6.2 (Light et al, 2000).…”
Section: Possible Patho-physiological Significance Of the Current Finmentioning
confidence: 99%
“…We began by examining the temporal dynamics of regulatory lipids at individual sites of exocytosis of MMP-9 in MCF-7 cells. In regulated exocytosis, the importance of regulatory lipids, PIP2 and DAG, are well documented as secondary messengers involved in several cellular signaling pathways [50], including the distinct steps of regulated exocytosis [28,31,51,59,71]; [35,44,46,62,63,72,73]. PIP2 is an important recruiting factor, priming secretory vesicles for exocytosis, by interacting with several essential exocytic proteins [71].…”
Section: Pma-induced Exocytosis Of Mmp-9 Accompanied By Transient Recmentioning
confidence: 99%